Experience with a cholinesterase histochemical technique for rectal suction biopsies in the diagnosis of Hirschsprung's disease - Trigg, P. H. (1974)
Cryostat sections from 160 rectal suction biopsies were stained for cholinesterases by the method of Karnovsky and Roots (1964) in an attempt to facilitate the diagnosis of Hirschsprung's disease. The method proved at least as reliable as experienced assessment of paraffin haematoxylin-eosin sections, and appeared to offer the advantages of reduced scanning fatigue and superior demonstration of the increased cholinesterase-positive nerves in Hirschprung's disease. Contrary to the findings of Meier-Ruge (1971) it was not possible to base a diagnosis on mucosal cholinesterase activity.